Functional Characterization of Clinically-Relevant Rare Variants in ABCG2 Identified in a Gout and Hyperuricemia Cohort - Toyoda, Yu; Mančíková, Andrea; Krylov, Vladimír; Morimoto, Keito; Pavelcová, Kateřina; Bohatá, Jana; Pavelka, Karel; Pavlíková, Markéta; Suzuki, Hiroshi; Matsuo, Hirotaka; Takada, Tappei; Stiburkova, Blanka (Cells, 2019)
ATP-binding cassette subfamily G member 2 (ABCG2) is a physiologically important urate transporter. Accumulating evidence demonstrates that congenital dysfunction of ABCG2 is an important genetic risk factor in gout and hyperuricemia; recent studies suggest the clinical significance of both common and rare variants of ABCG2. However, the effects of rare variants of ABCG2 on the risk of such diseases are not fully understood. Here, using a cohort of 250 Czech individuals of European descent (68 primary hyperuricemia patients and 182 primary gout patients), we examined exonic non-synonymous variants of ABCG2. Based on the results of direct sequencing and database information, we experimentally characterized nine rare variants of ABCG2: R147W (rs372192400), T153M (rs753759474), F373C (rs752626614), T421A (rs199854112), T434M (rs769734146), S476P (not annotated), S572R (rs200894058), D620N (rs34783571), and a three-base deletion K360del (rs750972998). Functional analyses of these rare variants revealed a deficiency in the plasma membrane localization of R147W and S572R, lower levels of cellular proteins of T153M and F373C, and null urate uptake function of T434M and S476P. Accordingly, we newly identified six rare variants of ABCG2 that showed lower or null function. Our findings contribute to deepening the understanding of ABCG2-related gout/hyperuricemia risk and the biochemical characteristics of the ABCG2 protein.
Keywords: senioři; běloši; Genetic Predisposition to Disease; biologický transport; ABC transportér z rodiny G, člen 2; gout susceptibility; Neoplasm Proteins; senioři nad 80 let; jednonukleotidový polymorfismus; přenašeče organických aniontů; HEK293 Cells; nádorové proteiny; multiple rare variant; Hyperuricemia; mladiství; Česká republika; ATP Binding Cassette Transporter, Subfamily G, Member 2; Biological Transport; Cohort Studies; Gout; WGA.; Middle Aged; mužské pohlaví; Adult; hyperurikemie; Organic Anion Transporters; Czech Republic; kyselina močová; kohortové studie; dítě; Child; heritability of serum uric acid; functional study; Aged, 80 and over; Child, Preschool; ženské pohlaví; European cohort; HEK293 buňky; předškolní dítě; Humans; urate transporter; Uric Acid; lidé středního věku; White People; exon sequence; dospělí; genetická predispozice k nemoci; ABCG2/BCRP; Female; Aged; common disease; Adolescent; dna (nemoc); lidé; Male; Polymorphism, Single Nucleotide